Rancang Bangun Sistem Pendeteksi Kebocoran Gas Berbasis Internet of Things di Lingkungan Rumah Tangga - Lukcy T Simanjuntak (Jurnal Nasional Teknologi Komputer, 2025)
This research aims to design and build an Internet of Things (IoT)-based gas leak detection system aimed at improving safety in the household environment. Gas leaks, which can potentially lead to fires and explosions, require quick and efficient detection. The developed system uses gas sensors connected to microcontrollers to monitor the concentration of hazardous gases, such as methane and propane, in real-time. Data from the sensor is sent via a wireless communication module to the mobile app, which allows users to receive instant notifications if a gas leak is detected. The test results show that the system is capable of detecting leaks with high accuracy and fast response times. Field trials also indicate that the system functions effectively in a wide range of environmental conditions. Feedback from users shows that the developed mobile app is easy to use and provides clear information about the status of gas leaks. This study concludes that IoT-based gas leak detection systems can be an effective solution to improve safety in households. It is hoped that this system can be widely applied to protect the public from the risk of gas leaks.